The Use of M-Learning: A Perspective of Learners’ Perceptions on M-Blackboard Learn - AlKhunzain, Abdulmohsin Suliman; Khan, Raja Muhammad Ishtiaq (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The life of the common to the students have changed due to spread of COVID-19 9 all around the globe. All the educational institutions were also set to be functioned remotely following the global instructions to meet the challenges to combat the COVID-19. The of current inquiry is the explore the male and female learners on the use of mobile phones for Blackboard learn. The Study survey method to collect the data. 68 participants of the medical majors of the CFY formed the sample for the present study. The findings of the study indicate that learners preferred to use M-blackboard. The results also indicated that backboard which is a form of e-learning can be beneficial if it is used with the traditional classroom teaching to get the potential benefits of the software.